Analysis Ballistic Flight and Design of Control System RKX200TJ/Booster at Rocket Booster and Climb Phases - Hakiki, Hakiki (Indonesian Journal of Aerospace, 2020)
The problem encountered while developing the RKX-200TJ/booster is the measurement of mass vehicle (center of gravity). The thrust line of the rocket booster does not coincide with the center of gravity can induce a pitch disturbance. By controlling the pitch parameter, the pitch disturbance phenomenon can be minimized. In this paper is presented the flight performance and dynamics analysis and the design of pitch and roll control system for RKX200TJ/booster during rocket booster and climb phase. The result indicates that the pitch disturbance can be reduced until decrease about 27% whereas roll angle ( ) can be damped at zero level ( ). Pitch angle ( ) can be maintained at angle 5° for climb phase. Although the one of moment arm case shows the static instability and uncontrollability during rocket booster phase, the control system can control vehicle the further phase. This simulation presented in X-Plane and Simulink. The PID controller is selected in control system design.